Theory of single and multiple interfaces the method of surface Green function matching - Garcia-Moliner, Federico (World Scientific Pub. Co., 1992)
Based on a scattering theoretic approach which effectively constitutes an extension of the Dyson or Lippman-Schwinger theories, Green functions constitute the backbone of a matching analysis. This analysis is applied to a wide range of models, materials and physical problems, from electronic structure of semiconductor superlattices or phonons in metal superlattices to surface Brillouin scattering, piezoelectric surface waves or interface waves in viscoelastic fluids